Analyzing EFL Students’ Intrinsic and Extrinsic Motivation in Grammar Learning through Quizizz - Agussalim, Devi Triani; Yunitari Mustikawati; Ryan Rayhana Sofyan; Tahir, Muhammad (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This study aims to analyze the level of EFL students’ intrinsic and extrinsic motivation in grammar learning after being taught using Quizizz, a digital game-based learning platform. The research employed a quantitative approach with a posttest-only quasi-experimental design. The participants were 60 eighth-grade students from MTs DDI Baru, divided into two groups: an experimental group receiving grammar instruction through Quizizz and a control group taught using conventional methods. A validated motivation questionnaire based on Self-Determination Theory was administered to both groups after the treatment. The results revealed that students in the experimental group demonstrated higher levels of both intrinsic and extrinsic motivation compared to the control group. These findings suggest that integrating Quizizz into grammar instruction can enhance students’ motivation by providing an interactive, engaging, and learner-centered learning environment. The study contributes to the growing body of literature on gamified learning in EFL contexts, particularly in the affective domain. Recommendations for future research include exploring long-term motivational impacts and comparing various digital learning platforms.